A educação ambiental em ações práticas de segurança alimentar e nutricional - Schneider , Mauri José (2022)
This research shows the participatory construction of knowledge, through an interdisciplinary and transdisciplinary process of Environmental Education in food security and nutrition in the context of agro-ecological literacy. The purpose of this research was to analyze the influence of Environmental Education and its capillarity effects for the processes of Nutritional Food Security in school food, within the Itaipu Binacional acting area, Brazilian territory. Therefore, an exploratory and descriptive research was adopted, having as base the methods the participatory research action. In this methodological context, the technical procedures of the data gathering were a questionary applied by google forms platform in the presential dynamics of people who learn practicing, in addiction to documentary research. The study corresponds to the place of action of an Institution, being 55 cities in the West of Paraná State, with a universe of 201 nutritionists and cooks taking part directly in the practicing processes. To attend the general objective were evaluated in the study, institutional documents, agreements and also the participatory action of the researcher together with the participating subject. As a result, it is noticed that the actions of Environmental Education in Food and Nutrition Security have financial incentives, thus the results of human resources worth mentioning by the logistics, strategies of mobilization, commitment of those involved and constituted networks. In the formative processes was remarked that the nutritionists and cooks had experiences, exchange of knowledge, sharing of experiences and improvements in school meals, although with limitations in working technical concepts with students and the identification of little product of family agriculture, mainly organic. In the healthy recipe pageant and in the production of the recipe book was identified the appreciation and self-esteem of the cooks, they being protagonists of a material as an eco-pedagogical instrument for ecological literacy. With these results was understood that the Environmental Education promoted an effect of rooting and capillarity in practical initiatives in Food and Nutrition Security, incentivizing ecological literacy through the dialogue of knowledge and contributing to the construction of a new socio-environmental reason in the territory, acting in participatory networks in the way that develops acknowledgement and relationships showing a new course for the dimensions of sustainability.